RIA analysis of GCITA (green corporate income tax adjustment) as a fiscal instrument to promote the implementation of green accounting - Dakwan Soaloon Harahap; Edy Suranta Sembiring (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The planet Earth has been facing the long-predicted impacts of climate change, which has resulted in changing weather patterns, land loss due to rising sea levels, more frequent forest fires, increasingly intense heat waves, and glacier retreat. The increased focus on climate change issues has called on accountants to support the recording, reporting, and management of companies so that they can adapt to climate change. Therefore, the implementation of green accounting needs to be encouraged through government policies because its impact can not only help companies manage environmental costs, but also strengthen their financial performance. Methods: This paper focuses on examining new fiscal policy opportunities to support the implementation of green accounting in Indonesia in order to address climate change challenges while improving corporate financial performance through Regulatory Impact Analysis (RIA). Findings: Based on the results of the RIA analysis, it is recommended that the government create a new fiscal policy, namely the Green Corporate Income Tax Adjustment (GCITA), because the benefits generated are greater than the costs incurred. GCITA is a policy that provides adjustments to the Corporate Income Tax (PPh) and Dividend Tax rates as an active policy tool to guide corporate behavior related to the implementation of green accounting. Conclusion: GCITA has strong potential to become a fiscal instrument to encourage the implementation of green accounting and strengthen sustainability commitments towards a green economy. This study is limited by its reliance on qualitative secondary data and a desk-based RIA framework. The analysis lacks quantitative fiscal modeling and empirical validation within the specific Indonesian economic context, which may affect the precision of the projected revenue impacts. Novelty/Originality of this article: The existence of new policy proposals that encourage the implementation of green accounting and the transition to a sustainable green economy that responds to global challenges.